Palmitylation of the influenza virus hemagglutinin (H3) is not essential for virus assembly or infectivity. - Jin, H (1996)
The C terminus of the influenza virus hemagglutinin (HA) contains three cysteine residues that are highly conserved among HA subtypes, two in the cytoplasmic tail and one in the transmembrane domain. All of these C-terminal cysteine residues are modified by the covalent addition of palmitic acid through a thio-ether linkage. To investigate the role of HA palmitylation in virus assembly, we used reverse genetics technique to introduce substitutions and deletions that affected the three conserved cysteine residues into the H3 subtype HA. The rescued viruses contained the HA of subtype H3 (A/Udorn/72) in a subtype H1 helper virus (A/WSN/33) background. Rescued viruses which do not contain a site for palmitylation (by residue substitution or substitution combined with deletion of the cytoplasmic tail) were obtained. Rescued virions had a normal polypeptide composition. Analysis of the kinetics of HA low-pH-induced fusion of the mutants showed no major change from that of virus with wild-type (wt) HA. The PFU/HA ratio of the rescued viruses grown in eggs ranged from that of virus with wt HA to 16-fold lower levels, whereas the PFU/HA ratio of the rescued viruses grown in MDCK cells varied only 2-fold from that of virus with wt HA. However, except for one rescued mutant virus (CAC), the mutant viruses were attenuated in mice, as indicated by a > or = 400-fold increase in the 50% lethal dose. Interestingly, except for one mutant virus (CAC), all of the rescued mutant viruses were restricted for replication in the upper respiratory tract but much less restricted in the lungs. Thus, the HA cytoplasmic tail may play a very important role in the generation of virus that can replicate in multiple cell types.